The Church in the Public Space: Lessons from the Exodus Church in Jürgen Moltmann’s Theology of Hope - Osei, Isaac Karkari; Obimpeh-Quayson, Emmanuel (Diligentia: Journal of Theology and Christian Education, 2024)
The ecclesial community's call to duty and ability to carry out its mission is centered on how relevant it must become to the existential realities of those living in the public sphere. Jürgen Moltmann makes what can only be considered as a concise statement when he states that, to make Christianity accessible to the masses, theology must openly uphold the universal concerns of God's coming Kingdom. The church, following its own faith principles, must demonstrate "general concern in the light of hope in Christ for the kingdom of God" by becoming "political in the name of the poor and the marginalized in a given society, by thinking critically about the religious and moral values of the societies in which it exists." Christian theology continues to be the mouthpiece of the church. This article's goal is to discuss Jürgen Moltmann's straightforward explanation of the church's public relevance in helping people remember why it exists in all forms of human sociality. This article's reflections aim to highlight the fact that the Christian church can only be seen to be fulfilling its mission when it is perceived as the voice of the voiceless, bringing God's fullness to human flourishing, and providing true meaning to human tranquillity in a difficult and uncertain world.